2020
DOI: 10.3390/ijerph17228680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics in Early Childhood Associated with a Nevus-Prone Phenotype in Adults from Tropical Australia: Two Decades of Follow-Up of the Townsville Preschool Cohort Study

Abstract: Having numerous melanocytic nevi increases melanoma risk. Few studies have enumerated nevi in children and re-examined them as adults. We aimed to determine if childhood nevus-counts predict nevus-prone adults, and further explore the relevance of host-factors and sun-exposure. Fifty-one Caucasian residents of Townsville (19.16° S, Queensland, Australia) had full-body nevus-counts aged 1–6 and 21–31 years-old. Sun-exposure was determined from questionnaires. Children in the upper-quartile of nevus-counts acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Seborrhoeic keratosis is reported to associate with sun exposure and tanning (Del Rosso, 2017). Sunlights have some influence on the occurrence of Melanocytic naevi (Barsoum and Harrison, 2020). The common naevi distribution pattern over the skin is consistent with the sun exposure habit (Carli et al, 1998).…”
Section: Introductionsupporting
confidence: 60%
“…Seborrhoeic keratosis is reported to associate with sun exposure and tanning (Del Rosso, 2017). Sunlights have some influence on the occurrence of Melanocytic naevi (Barsoum and Harrison, 2020). The common naevi distribution pattern over the skin is consistent with the sun exposure habit (Carli et al, 1998).…”
Section: Introductionsupporting
confidence: 60%
“…Infants and children are particularly vulnerable to the effects of excessive sun exposure [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and UVR-related changes in an infant’s skin have been shown to begin accumulating from their first summer [ 31 ]. Migrants relocating to UVR-intense climates after ten years of age develop fewer MN and are less likely to develop melanoma as adults than native-born residents or migrants who arrive earlier in life [ 24 , 32 ], suggesting that childhood is a critical time for the influence of sun exposure in MN development [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 ]. Children raised in NQ acquire common MN, large MN, and atypical MN earlier and in higher numbers (up to 252 common MN by age six) than children raised in less intense solar UVR environments [ 27 , 28 , 29 , 30 , 33 ], putting them at increased risk of developing melanoma in the future [ 5 , 17 , 19 , 20 , 21 , 24 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total number of sunburns experienced by these young children since birth was, however, an independent predictor of the presence of MN that were at least five millimeters in diameter by their annual follow-up examination [ 29 ]. More recently, our 20+-year follow-up of this pediatric cohort found that the rate of acquisition of new MN between early childhood and the third decade of life was significantly higher in individuals who had experienced a sunburn before seven years of age, particularly if the sunburn was severe or had occurred annually during early childhood [ 35 ]. Other recent epidemiological studies of MN [ 26 , 34 ], including a cross-sectional analysis of baseline data from the “Study of Nevi in Children” (SONIC) by Satagopan and co-workers [ 34 ], corroborate the findings of earlier studies of MN, demonstrating the importance of sunburn in early life and host factors such as sun sensitivity in their development [ 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation